Optimization of Manganese Peroxidase Enzyme Production from Pleurotus ostreatus Mushroom in Organik Medium - Afroza, Faiza; Putri, Dwi Hilda; Irdawati, Irdawati; Farma, Siska Alicia; Andriani, Ade; Saskiawan, Iwan (Jurnal Biologi Tropis, 2025)
The production of manganase peroxidase (MnP, a key lignolityc enzyme with broad applications in bioremediation and industrial processing, can be significantly enhanced trough the optimation of medium composition and fermentation time. This study aimed to determine the optimal organic medium, concentration, and incubation period for MnP production by Pleurotus ostreatus. Various plant-base substrates such as brown rice, mungbean, almond, red bean soybean, and potato dextrose broth (PDB) were evaluated using a descriptive method, withvthe obtained data calculated and analyzed in Excel, and the results presented in the form of diagrams. The results showed that brown rice medium is the most optimal medium to support the produvction of MnP (981,6 U/L), attribute to its high carbohydrate and micronutrien content. Futher optimization revealed that a consentration of 7,5%, while fermentation time optimization indicated that the 9th day was optima, producing up to 3207,1 U/L of enzyme activity. These findings suggest that selecting the right substrate and fermentation conditions can substantially improve MnP synthesis by P. ostreatus, making it a promising strategy for sustainable enzyme production and future biotecnological application. For future studies, it is recommended to explore large scale fermentation systems and alternative agro industrial waste susbtrates to further enhance enzyme yield and cost efficiency